Challenges in applying IR4.0 technologies to improve organizational structure and positions: the case of Malaysian public agencies - Syafini Samsudin; Mohd Hizam Hanafiah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Despite the challenges, the Fourth Industrial Revolution (IR4.0) offers prospects for enhancing public service delivery. This article identifies the challenges in applying IR4.0 technologies to improve organisational structure and roles of Malaysian public agencies. The Socio-technical Systems Theory, Learning Organization Theory, and Theory of Disruption are discussed as a theoretical framework of this article. Employing the qualitative grounded theory methodology, data was collected from 26 public officials through interviews and a focus group discussion. The results reveal seven themes categorised into internal and external challenges. The internal challenges include human resources, financial resources, work process, digital data, laws and regulations, and the agency’s function, while public perception forms the sole external challenge. Seven research propositions have been developed to propose the relationship between these challenges and the implementation of IR4.0 technologies in improving organizational structure and positions. The research provides empirical evidence on the challenges facing public agencies in using IR4.0 technologies to improve organizational structure and positions, thus offering recommendations that public officials must reformulate and restructure their approach in managing human resources during IR4.0.